Integrating content and language in teacher development: CLIL for academic vocabulary growth in Algeria - Tobbi, Saida (Universitas Mulawarman, 2026)
This study investigates the impact of Content and Language Integrated Learning (CLIL) on academic vocabulary development and disciplinary understanding among newly recruited teachers at Batna 2 University, Algeria. Conducted within the framework of the national teacher development program, the research examined how integrating English into the teaching of research methodology could enhance both linguistic competence and conceptual learning. A mixed-methods framework integrated quantitative and qualitative approaches, including an Academic Vocabulary Test, a corpus of participants’ written tasks, and reflective questionnaires. Sixty-eight teachers from twenty-three academic departments participated in eight weeks of CLIL-oriented instruction. Quantitative findings revealed notable improvements in receptive and productive academic vocabulary (t(67) = 14.27, p < .001, d = 1.37), alongside marked increases in lexical diversity, sophistication, and density. Thematic analysis indicated greater lexical awareness, cognitive engagement with research concepts, and positive perceptions of English as a medium for disciplinary learning. The results suggest that CLIL-oriented pedagogy promotes deep processing of academic lexis and supports Algeria’s ongoing transition toward English-medium higher education. Embedding content and language objectives within teacher education programs can therefore strengthen linguistic competence and disciplinary literacy in multilingual academic contexts.